Prostanoid Receptor Subtypes and Its Endogenous Ligands with Processing Enzymes within Various Types of Inflammatory Joint Diseases - Mohammed A. Al-Madol; Mohammed Shaqura; Thilo John; Rudolf Likar; Reham Said Ebied; Magdi M. Salih; Sascha Treskatsch; Michael Schäfer; Shaaban A. Mousa (Hindawi Limited, 2020)
A complex inflammatory process mediated by proinflammatory cytokines and prostaglandins commonly occurs in the synovial tissue of patients with joint trauma (JT), osteoarthritis (OA), and rheumatoid arthritis (RA). This study systematically investigated the distinct expression profile of prostaglandin E2 (PGE2), its processing enzymes (COX-2), and microsomal PGES-1 (mPGES-1) as well as the corresponding prostanoid receptor subtypes (EP1-4) in representative samples of synovial tissue from these patients (JT, OA, and RA). Quantitative TaqMan®-PCR and double immunofluorescence confocal microscopy of synovial tissue determined the abundance and exact immune cell types expressing these target molecules. Our results demonstrated that PGE2 and its processing enzymes COX-2 and mPGES-1 were highest in the synovial tissue of RA, followed by the synovial tissue of OA and JT patients. Corresponding prostanoid receptor, subtypes EP3 were highly expressed in the synovium of RA, followed by the synovial tissue of OA and JT patients. These proinflammatory target molecules were distinctly identified in JT patients mostly in synovial granulocytes, in OA patients predominantly in synovial macrophages and fibroblasts, whereas in RA patients mainly in synovial fibroblasts and plasma cells. Our findings show a distinct expression profile of EP receptor subtypes and PGE2 as well as the corresponding processing enzymes in human synovium that modulate the inflammatory process in JT, OA, and RA patients.